Effectiveness of a school-based intervention to manage overweight and obesity among adolescents in Seremban, Malaysia: a cluster randomized controlled trial - Lai, Wai Kent (Elsevier, 2023)
The aim of the study was to evaluate the effectiveness of a school-based intervention programme among overweight and obese adolescents in Seremban, Negeri Sembilan, Malaysia. A cluster randomised controlled trial was conducted to evaluate the effect of the intervention (n = 200) and compared with control group (n = 200). The intervention was developed based on social cognitive theory, conducted in a group based, five-session of face-to-face, bi-weekly for 10 weeks. The primary outcomes were body mass index (BMI) and BMI-for-age z-scores (BAZ), whereas the secondary outcomes were breakfast consumption, physical activity level, self-efficacy, and body satisfaction. T-tests and generalized linear mixed model analysis were used to examine the effectiveness of the intervention at baseline, immediate post-intervention, and 3-month post-intervention, while controlling for covariates. A significant intervention effect was found in reducing BMI and BAZ. BMI of the participants in the intervention group was reduced from 28.10 kg/m2 to 27.93 kg/m2, and further decreased to 27.80 kg/m2, while BAZ was reduced from 2.19 to 2.12, and further decreased to 2.07, from baseline to immediate post-intervention, and 3-month follow-up, respectively. Furthermore, there was significant improvement in breakfast consumption frequency, physical activity scores, healthy eating and weight self-efficacy scores, perceived physical activity self-efficacy scores, and body discrepancy scores as compared with the control group. The integrated school-based intervention programme was effective in reducing BMI and BAZ among overweight and obese participants. The results suggested that this programme could be integrated as one of the regular school co-curricular programmes.